Sugarcane Woolly Aphid, Ceratovacuna Lanigera - An Invasive Pest of Sugarcane and its Management in Bangladesh (Journal of the Asiatic Society of Bangladesh, Science, 2025)
Study was conducted in homestead garden of Patuakhali Science and Technology University (PSTU) campus, Patuakhali during the period from November 2016 to October 2017. Results revealed that the length and width of the apterous adult female was 1.76 mm and 1.06 mm, respectively while the length and width of the alate adult was 2.09 mm and 6.4 mm, respectively. The nymphal stage varies from 15.8 (minimum) days to 32 (maximum) days of apterous, whereas of alate form the period is little longer, up to 40 days. The maximum population density of woolly aphid was observed in vegetative stage (47.12/2.5 sq.cm.) and the lowest population density was recorded in seedling stage (7.23/2.5 sq.cm.). The highest percent leaf area occupied by sugarcane woolly aphid was observed at vegetative stage (58.13%/leaf) and the lowest percent leaf area occupied by sugarcane woolly aphid was recorded in seedling stage (27.14%/leaf). No significant difference was found among leaves treated with 4 insecticidal treatments. But the lowest number (0.33 aphid/sq. cm) of woolly aphid per square cm area was found in leaf treated with Biotap plus extra 95EC @ 0.2 g/L of water followed by T4 (0.67 aphid/sq. cm) where Fija 70WG @ 0.074 g/L of water was sprayed. The highest number of woolly aphid was observed in untreated control treatment (41.33 woolly aphid/sq. cm). The highest percent reduction (99.20%) of woolly aphid over control was found in leaves treated with Biotap plus extra 95EC @ 0.2 g/L of water. Likewise, the percent reduction of leaf area occupied by woolly aphid was recorded maximum (99.41%) in leaves treated with Biotap plus extra 95EC @ 0.2 g/L of water while minimum percent (98.20%) was in leaves treated with Voliam flexi 300SC @ 0.5 ml/L of water. Application of Biotap plus extra 95EC @ 0.2 g/L of water could be the best treatment for the management of sugarcane woolly aphid. J. Asiat. Soc. Bangladesh, Sci. 51(1): 39-50, June 2025